The development of the Islamic sultancy in Indonesia - Supitayanti Supitayanti; Biron Najwa Royan; Nasikhin Nasikhin; Fihris Fihris (Histeria Jurnal: Ilmiah Soshum dan Humaniora, 2023)
This study aims to analyze the development of Islamic sultanates in Indonesia. This study uses a qualitative approach with data collection techniques in the form of literature studies. The collection of materials related to research comes from books, scientific journals, literature and other publications that are worthy of being used as sources for research. The results of this study indicate that The Islamic sultanates in Indonesia have different styles in each region; The glory factor of the Islamic sultanate in Indonesia was one of them influenced by the existence of the Archipelago's maritime trade traffic routes passed by traders from Arab, Persian, Indian, and even Chinese who were predominantly Muslim; One of the factors behind the decline of the Islamic empire in Indonesia was the influx of western nations, such as the Portuguese, Spanish, Dutch and British who came to Indonesia. Thus it can be concluded that the Islamic sultanates in Indonesia had different styles in each region, so that the differences in these styles became a distinct characteristic of the many Islamic sultanates in Indonesia. This study is important to study in order to add to the sources of study of Islamic history in Indonesia, especially the lack of themes regarding the development of Islamic sultanates in Indonesia.